2008
DOI: 10.1293/tox.21.9
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced Phospholipidosis -Pathological Aspects and Its Prediction

Abstract: Drug-induced phospholipidosis (PLDsis) is an excessive accumulation of polar phospholipids in cells or tissues/organs caused by xenobiotics. Numerous drugs and chemicals are capable of inducing the storage disorder in animals and humans; however, despite their diverse pharmacological activities, each of these drugs shares common physicochemical properties: a hydrophobic aromatic ring structure on the molecule and a hydrophilic side chain with a charged cationic amine group and therefore are in the group of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 74 publications
(85 reference statements)
2
84
0
6
Order By: Relevance
“…Thus, the presence of the histidine tag itself did not affect the electrostatic interaction. In addition, the drug AMD, positively charged under physiological conditions, shows a high affi nity to phospholipids via hydrophobic as well as hydrophilic interactions ( 19 ). Thus, AMD could diminish the negative charge produced by anionic lipids incorporated into liposomes and, as a result, weaken the electrostatic interaction between the LPLA2 and the lipid membranes in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the presence of the histidine tag itself did not affect the electrostatic interaction. In addition, the drug AMD, positively charged under physiological conditions, shows a high affi nity to phospholipids via hydrophobic as well as hydrophilic interactions ( 19 ). Thus, AMD could diminish the negative charge produced by anionic lipids incorporated into liposomes and, as a result, weaken the electrostatic interaction between the LPLA2 and the lipid membranes in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have tentatively suggested that drug-induced PLD itself likely has no major pathological consequences. [107,[200][201][202] Nevertheless, the correlation between hepatic toxicity and PLD has renewed interest in the mechanism of PLD and in high-throughput screening methods for detecting PLD. In particular, the PLD-inducing cationic amphiphilic drugs form the only group of drugs frequently associated with classical steatohepatitis.…”
Section: Why Is Phospholipidosis Of Interest?mentioning
confidence: 99%
“…The mechanism for PPL development is a druginduced inhibition of lysosomal phospholipase activity [49]. Due to the potential organ dysfunction as a result of PPL, in addition to the conventional identification of lamellar bodies by electron microscopy, several biomarkers were established for screening tests in the preclinical stages and clinical phases [50]. A number of 17 genes were identified in HepG2 cells as potential biomarkers of PPL [51].…”
Section: Drugs With Phospholipidosis Inducing Potentialmentioning
confidence: 99%